MANAGING PLURALISM, DEFENDING RELIGIOUS MINORITY GROUPS - Halili, (International Journal of Psychosocial Rehabilitation, 2020)
Religious pluralism becomes sociological basic of “Bhinneka Tunggal Ika”, national motto of Indonesia. It demands a politic of religion which is necessary for managing Indonesian pluralism on one hand and defending religious minority groups on the other. Regarding to issue, there are numbers of problem. First inconsistence of governmental regulations against constitutional provisions on freedom of every citizen to follow any religion and worship according to his/her religion and faith. Second, strengthening of religious conservatism leading to violent extremism which shows ineffectiveness of state policies endangering the rights of religious minority groups. Third, politicking of religious identity and sentiment in electoral politics.